PREVALENCE AND RISK FACTORS OF SEVERE POSTPARTUM HEMORRHAGE IN CESAREAN SECTION DELIVERIES IN A TERTIARY CARE HOSPITAL, MUZAFFARABAD - Nosheena Akhter Shabbir; Uzma Khwaja; Madiha Saleem; Hina Pirzada; Seemab Zafar; Kainat Rashid (Journal of Population Therapeutics and Clinical Pharmacology, 2021)
Background: In developed countries, the rate of severe postpartum hemorrhage is increasing, which is a major concern for public health due to its impact on maternal health. Study objective: This study aimed to determine the frequency of severe postpartum hemorrhage and the contributing factors. Methods: A retrospective cohort study was conducted to explore the common risk factors associated with postpartum bleeding following cesarean deliveries in a tertiary care hospital. This study was conducted from January 2021 to July 2021 in the Department of Gynecology, Tertiary Care Hospital, in Muzaffarabad. Results: The average age of the mothers in the study was 29.4 years. Out of 2400 cases, 66.7 percent were elective cesarean sections, while 33.3 percent were emergency surgeries. Diabetes 7.5 percent, HTN (hypertension) 12.5 percent, emergency C-sections 33.3 percent, and prolonged surgery duration were the contributing risk factors. Surgical procedures that last more than an hour are the leading causes of severe postpartum hemorrhage. There is a significant association between risk factors like hypertension and severe postpartum hemorrhage. Conclusion: It was concluded that risk factors like hypertension, prolonged surgeries, and diabetes are leading risk factors for the incidence of severe postpartum hemorrhage.